The role of declining ataxia-telangiectasia-mutated (ATM) function in oocyte aging - Suzuki, R; Tan, X; Szymanska, KJ; Kubikova, N; Perez, CA; Wells, D; Oktay, KH (Springer Nature [academic journals on nature.com], 2024)
Despite the advances in the understanding of reproductive physiology, the mechanisms underlying ovarian aging are still not deciphered. Recent research found an association between impaired ATM-mediated DNA double-strand break (DSB) repair mechanisms and oocyte aging. However, direct evidence connecting ATM-mediated pathway function decline and impaired oocyte quality is lacking. The objective of this study was to determine the role of ATM-mediated DNA DSB repair in the maintenance of oocyte quality in a mouse oocyte knockdown model. Gene interference, in vitro culture, parthenogenesis coupled with genotoxicity assay approaches, as well as molecular cytogenetic analyses based upon next-generation sequencing, were used to test the hypothesis that intact ATM function is critical in the maintenance of oocyte quality. We found that ATM knockdown impaired oocyte quality, resulting in poor embryo development. ATM knockdown significantly lowered or blocked the progression of meiosis in vitro, as well as retarding and reducing embryo cleavage after parthenogenesis. After ATM knockdown, all embryos were of poor quality, and none reached the blastocyst stage. ATM knockdown was also associated with an increased aneuploidy rate compared to controls. Finally, ATM knockdown increased the sensitivity of the oocytes to a genotoxic active metabolite of cyclophosphamide, with increased formation of DNA DSBs, reduced survival, and earlier apoptotic death compared to controls. These findings suggest a key role for ATM in maintaining oocyte quality and resistance to genotoxic stress, and that the previously observed age-induced decline in oocyte ATM function may be a prime factor contributing to oocyte aging.